Strategies to Improve the Attractiveness of Sam Poo Kong Temple As Cultural Tourism Site of Semarang City, Central Java, Indonesia - Ikasari, Hertiana (Journal of Indonesian Tourism and Development Studies, 2021)
Culture plays a significant role in tourism. Indonesian tourism sets its regional cultures as one of its products' mainstays. The development of cultural tourism is one of the focuses in national tourism policy. Sam Poo Kong Temple is one of the popular cultural tourism destinations in Semarang city. Besides the many benefits of the existence of Sam Poo Kong temple, there are also some problems with the presence of some tourist complaints. These complaints indicate that there is tourists' dissatisfaction with Sam Poo Kong temple. When tourists' satisfaction is not highly concerned, it will reduce the attractiveness of Sam Poo Kong Temple. This study aims to analyze the strategy to improve the attractiveness of Sam Poo Kong Temple as a cultural tourism object in Semarang city. The respondents in this study are domestic tourists. The data will be collected by using a questionnaire. This research was analyzed using Importance-Performance Analysis (IPA). The results obtained show that the first performance priority to be improved is information attributes about the events held in Sam Poo Kong Temple through printed, electronic and social media and employee service quality attributes. This study suggested that, first, it needs to conduct various promotion forms of Sam Poo Kong Temple to improve the performance of attributes whose high priority. One of the easiest and the most inexpensive promotions is through social media. Second, it is necessary to improve the quality of human resources through both formal and informal training and HR development. Keywords: Cultural tourism strategy, importance-performance analysis, Sam Poo Kong Temple, tourism attractiveness, tourist satisfaction.